Biofilm production of candida species isolated from antenatal women with vulvovaginal candidiasis - KANISHKA HRISHI DAS; V. MANGAYARKARASI; MAITRAYEE SEN (International Journal of Pharma and Bio Sciences, 2019)
Vulvovaginal candidiasis (VVC) is a disguising infection in an antenatal woman. Candida species are yeast-like fungi present as normal flora in female genitalia and cause infection in individuals with underlying immunocompromised conditions. Several virulence factors are present in Candida species such as production of biofilm, secreted aspartyl proteinase (SAP), phospholipase, lipase, esterase and hemolysin. Biofilm is characterized as organized microbial networks that are connected to a surface and covered in a framework of exo-polymeric material which is responsible for virulence. The aim of this study was to demonstrate the in vitro biofilm forming abilities of Candida species isolated from antenatal women with vulvovaginal candidiasis. This was a prospective study carried out in SRM Medical College Hospital & Research Centre, Chennai, India, from March 2017 to December 2018. A total number of 300 vaginal swabs were collected from antenatal women suspected for symptomatic and asymptomatic vulvovaginal candidiasis. Samples were subjected to Candida species identification. Biofilm was detected by microtiter plate method. Totally 120 Candida species were isolated. Out of 120 Candida isolates, Candida albicans were 44 (37%) and Non-albicans Candida (NAC) were 76 (63%). Among NAC isolates C. krusei was the highest biofilm producer (90%), trailed by C. tropicalis (82%), C. glabrata (77%), C. parapsilosis (75%) and C. albicans (68%). The present data shows that the prevalence of NAC was higher than that of C. albicans. The Candida isolated from symptomatic antenatal women was found to produce more biofilm than that isolated from asymptomatic women.